Faktor-Faktor Keterlaksanaan Merdeka Belajar Pada Program Studi TKR SMK N di Blitar - Sulistyono, Budhi; Nurhadi, Didik; Widiyanti, Widiyanti (Jurnal Pendidikan Vokasi Otomotif, 2024)
The implementation of Merdeka Belajar (MB) brings fundamental changes to Vocational High Schools (VHS). The MB curriculum that is implemented needs to be approached with a deep understanding of the concepts and processes. Thus, many factors influence its implementation. This research aims to analyze the factors in implementing independent learning in vocational schools. This research uses a qualitative approach with a multi-case study at two Public Vocational High Schools (PVHS) in Blitar through in-depth interviews supported by observation and documentation. The research results show that the independent curriculum implemented in PVHS has obstacles in the form of teacher misconceptions and difficulties in synchronizing the curriculum in Light Vehicle Engineering (LVE) with industry. The learning model used in LVE subjects to train students to work independently is PjBL. Meanwhile, guest teachers from industries are invited to provide training and insight to teachers and students. Furthermore, internships are carried out in LVE workshops and industry. Meanwhile, student competency tests are carried out involving the career center and school certification. LVE learning technology updates and graduate absorption also influence this. In conclusion, the implementation of the MB curriculum at VHS is determined by teacher awareness and leadership strategy choices.